Examining the influence of community belonging on marijuana use among youth living in British Columbia, Canada. (13th March 2014) - Duff, Putu; Muldoon, Katherine; Toma, Owni; Richardson, Chris G.
Abstract: Background : Using cross-sectional data from the Canadian Community Health Survey (2007–2008), this study aimed to examine the impact of community belonging on marijuana use among British Columbian youth aged 12–24. Methods : Bivariable and multivariable multinomial logistic regression was used to examine the association between self-perceived community belonging and youth marijuana use (i.e. never, tried once and more than once lifetime use), and stratified by high and low adult marijuana use regions to determine if the relationships varied by the extent of adult marijuana use in each region. Results : Of 2095 youth respondents, 21.8% had used marijuana at least once in the past year, with the majority (70.9%) reporting a strong sense of community belonging. Weak community belonging increased youth's odds of initiation [Adjusted odds ratio (AOR) = 1.74; 95% Confidence Interval (CI) 1.18–2.56] and odds of more-than-once lifetime use (AOR = 1.40; 95% CI 1.10–1.79), and these associations were increased in regions where adult marijuana use was high. Conclusion : These findings suggest an association between weak sense of community belonging and youth marijuana use, and that use in the general population may increase this relationship. There is a need to better understand how youth interpret "community belonging", and further explore the relationship between marijuana availability and youth use.